Nomenclatural notes on a variety of Orthoptera - Braun, Holger (Zootaxa, 2024)
This short paper resolves some synonymic issues, mostly within neotropical Tettigoniidae, that arose from the migration of Orthoptera Species File to a new software platform. Furthermore, the preoccupied name Ommatoptera is replaced by its junior synonym Pseudotanusia and Conocephalus macroxiphus is moved from Ruspolia to Neoconocephalus. Moreover, new names are proposed for primary or secondary homonyms among a species of tree cricket from China and seven species of grasshoppers from China, Australia and Africa. Micropterellus is proposed as substitute name for Micropterus in the Pyrgomorphidae.